D-mannose promotes diabetic wound healing through inhibiting advanced glycation end products formation in keratinocytes - Luo, Jialiang; Wu, Tianxing; Zhang, Jing; Liang, Zhicheng; Shao, Weijie; Wang, Di; Li, Lei; Zuo, Daming; Zhou, Jia (Molecular Medicine, 2025)
Diabetic chronic foot ulcers pose a significant therapeutic challenge around the world, resulting in adverse effects and complications in patients. D-mannose is enriched in cirtus peel and exerts beneficial effects among various diseases, especially against inflammation-related disorders.